Articaine: dental practitioner use, basis of perception and evidence-based dentistry-a cross-sectional study - Erica Martin; Andrew Lee; Ernest Jennings (Nature Publishing Group, 2022)
Abstract Background Limited data exist on dental practitioner use and perceptions of articaine. This study is a cross-sectional survey of dental practitioners from January, 2021 to ascertain the extent of their use of the dental local anaesthetic, articaine, the basis of their perceptions about articaine and whether current practices are in line with recent evidence regarding articaine safety and efficacy. Method An anonymous survey was designed using the SAP Qualtrics Core XM software platform and a survey link was disseminated from December 2020 to January 2021 via social media. The survey was designed as a five minute, anonymous, online questionnaire including a plain language information sheet, request for participant consent and 14 questions. Data were entered onto a Microsoft™ Excel spreadsheet and analysed qualitatively, isolating the answers into recurrent themes. Results Sixty percent of the surveyed dental practitioner used articaine as their preferred dental anaesthetic. Twenty-three percent of the dental practitioner surveyed used articaine for all of their dental procedures including inferior alveolar nerve blocks, while 40% of respondents used articaine for all their dental procedures except inferior alveolar nerve blocks. The predominant basis of dental practitioner uses and perception of articaine were their countries dental guidelines. Conclusion Despite the latest findings that articaine is as safe and more efficacious as lidocaine for all routine dental treatment, 40% of survey respondents avoided articaine use for inferior alveolar blocks. Our study recognises a discrepancy between reported clinical practice and current research evidence. Further research and clarifications are needed to achieve ubiquitous practice of evidence-based dentistry.